2017
DOI: 10.1007/s00011-017-1026-6
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic efficacy of platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio in ovarian cancer

Abstract: According to the findings of our study, both PLR and NLR seem to be promising screening and prognostic factors of epithelial ovarian cancer. The actual diagnostic cut-off values remain, however, undefined until now. Despite their limited sensitivity and specificity, they might be useful in the future as adjunct biomarkers for the detection and surveillance of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 49 publications
4
31
1
1
Order By: Relevance
“…Our study is the first to provide data for patients from Northeast China with advanced EOC. Other published studies analyzing the data of foreign patients outside China had the consistent conclusion with us [4, 15, 16, 23-25]. …”
Section: Discussionsupporting
confidence: 70%
“…Our study is the first to provide data for patients from Northeast China with advanced EOC. Other published studies analyzing the data of foreign patients outside China had the consistent conclusion with us [4, 15, 16, 23-25]. …”
Section: Discussionsupporting
confidence: 70%
“…They commented on the limited sensitivity and specificity, that might be limiting its use only as adjunct biomarkers for the detection of the disease. 15 The Elevated pretreatment PLR, as referred to in our work , could be an unfavorable prognostic factor for clinical outcomes in patients with ovarian cancer, which was also concluded by Chuan T et al 16 Yildrim MA et al reported no significant difference between early and late stage disease regarding platelet count, lymphocytic count and PLR. 17 The results of Kokcu A et al reported a significant elevation of both platelet counts, and PLR as well as a significant direct correlations with CA125, and a significant rise of PLR with advanced stage disease.…”
supporting
confidence: 84%
“…Elevated platelet counts and thrombocytosis have been shown to actively affect tumor growth and metastasis in ovarian cancer . By contrast, the few studies that have investigated the use of platelet count or PLR in diagnosing endometriosis did not find a significant relationship .…”
Section: Discussionmentioning
confidence: 87%
“…Indicators of local and systemic inflammatory response, such as WBCs, neutrophils, and lymphocytes have been proposed as key factors in the pathogenesis of both ovarian cancer and endometriosis. Reportedly, NLR or NLR combined with CA125, can be more effective in diagnosing cancer or endometriosis as compared with CA125 alone . Cho et al .…”
Section: Discussionmentioning
confidence: 99%